2020
DOI: 10.1111/jdv.16227
|View full text |Cite
|
Sign up to set email alerts
|

Acral lentiginous melanoma: a single‐centre retrospective review of four decades in East‐Central Europe

Abstract: Background Acral lentiginous melanoma (ALM) occurs on the palms, soles and subungual surface and has poor prognosis. It is uncommon in the Caucasian population and has remained unreported in East‐Central Europe. Objectives Our aim was to collect data from East‐Central Europe by analysing the demographic and clinicopathologic features of patients with ALM and comparing data with the reports in literature. Methods We conducted a single‐centre, retrospective review between 1976 and 2016 at one of the largest mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…In this study, the median age at diagnosis in the training cohort and validation cohort was 65 and 66 years, respectively, and the interval between quartiles was 54–76 years old, which was similar to the results of Csányi’s study, indicating that ALM mainly affected the elderly. 24 It has been confirmed that elderly melanoma patients have a distinct natural history of disease in AJCC stages I, II, and III, with higher morbidity and mortality, 25 Therefore, the most likely reason for the influence of age on patient overall survival in this study was the inclusion of a large number of ALM patients with AJCC I, II, and III stage. In addition, there may be other reasons for this result, such as the decreased immune capacity of elderly patients, the increase of chronic inflammatory markers, and the elderly patients are more susceptible to more aggressive tumor invasion, which lead to the decreased survival rate.…”
Section: Discussionmentioning
confidence: 66%
“…In this study, the median age at diagnosis in the training cohort and validation cohort was 65 and 66 years, respectively, and the interval between quartiles was 54–76 years old, which was similar to the results of Csányi’s study, indicating that ALM mainly affected the elderly. 24 It has been confirmed that elderly melanoma patients have a distinct natural history of disease in AJCC stages I, II, and III, with higher morbidity and mortality, 25 Therefore, the most likely reason for the influence of age on patient overall survival in this study was the inclusion of a large number of ALM patients with AJCC I, II, and III stage. In addition, there may be other reasons for this result, such as the decreased immune capacity of elderly patients, the increase of chronic inflammatory markers, and the elderly patients are more susceptible to more aggressive tumor invasion, which lead to the decreased survival rate.…”
Section: Discussionmentioning
confidence: 66%
“…It was demonstrated that the big toe was generally affected in SUM (4). Average tumor thickness has been estimated to be between 3.1 mm and 6 mm in the literature (3)(4)(5)(6), and the tumor thickness was approximately 2.0 mm in this case. Often, it first appears as longitudinal melanonychia, which may progressively extend or progress to thickening, splitting, or destruction of the nail plate with pain and inflammation (1, 2).…”
Section: Discussionmentioning
confidence: 59%
“…Several previous investigations revealed that ALM represents a very aggressive CM subtype (Bello et al 2013;Csányi et al 2020;Duarte et al 2017). The question is, however, whether ALM really represents a biologically more aggressive CM subtype per se or whether the worse outcome observed in this melanoma subset is just due to delayed diagnosis and advanced stage at first presentation?…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many research groups have observed that overall survival rates of ALM patients are lower when compared to patients with SSM alone or all melanoma subtypes, except for ALM (Bello et al 2013 ; Csányi et al 2020 ; Duarte et al 2017 ; Huang et al 2020 ; Kuchelmeister et al 2000 ; Lv et al 2016 ; Phan et al 2006 ; Slingluff et al 1990 ). Using SSM as the reference category, El Sharouni et al ( 2020 ) observed adjusted hazard ratios of 1.26 (95% CI 1.06–1.50) for ALM.…”
Section: Discussionmentioning
confidence: 99%